2010
DOI: 10.1111/j.1752-7325.2009.00159.x
|View full text |Cite
|
Sign up to set email alerts
|

Performance of Atraumatic Restorative Treatment (ART) depending on operator-experience

Abstract: For The Republic of The Gambia--especially for areas with underdeveloped medical infrastructure--training and assignment to perform ART can be recommended for auxiliary dental staff of Community Oral Health Workers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
24
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(26 citation statements)
references
References 19 publications
1
24
0
1
Order By: Relevance
“…While some authors described an operator‐effect between dental therapists and dentists (30), other investigators did not find significant differences (31). The absence of an operator‐effect between the Community Oral Health Workers of our study and dentists was published elsewhere (6).…”
Section: Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“…While some authors described an operator‐effect between dental therapists and dentists (30), other investigators did not find significant differences (31). The absence of an operator‐effect between the Community Oral Health Workers of our study and dentists was published elsewhere (6).…”
Section: Discussionsupporting
confidence: 55%
“…ART combines a less traumatic technique because of manual cavity preparation with the use of a glass‐ionomer cement as an adhesive and fluoride releasing restoration material (4, 5). The clinical skills are simple, and therefore, ART can be performed by dental auxiliaries (6). In areas without primary oral health care, however, carious teeth often remain untreated or are extracted in case of complications (7).…”
mentioning
confidence: 99%
“…Training dental personnel in ART is a necessity if one wants to provide quality preventive and restorative care. Also the type of dental personnel may be a factor in the success of ART restorations with dentists performing better than nondentists [26] . ART is considered one of the treatments that constitute modern caries management within the concept of Minimal Intervention Dentistry [7] , but it should not be looked at lightly.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, only one dentist trained in the ART technique provided the restorations, but it is likely that a hygienist also properly trained in the technique could produce the same output. Other studies have shown no difference in restoration placement time between properly trained operators , whether they are fully trained dentists or not. However, a revision of the dental hygiene curriculum would be necessary in countries where these professionals do not perform restorations such as Ireland, giving an emphasis to the ART technique.…”
Section: Discussionmentioning
confidence: 93%